UJI MATERIIL PERATURAN PERMENKUMHAM NOMOR 1 TAHUN 2018 TENTANG PARALEGAL TERHADAP UNDANG-UNDANG NOMOR 18 TAHUN 2003 TENTANG ADVOKAT - Asnawi Asnawi; Arif Nurrohman (LPPM Universitas Bina Bangsa, 2022)
Legislation has a strategic role in the state of Indonesia, which is a state of law in running a country for the protection of human rights based on law. This is the basis of the state as well as a strategy to achieve the objectives as set out in the constitution. In the amendments to the Constitution, the two state institutions, namely the Supreme Court and the Constitutional Court, expressly authorizes the judicial review of legislation. In formulating the problem, it is to find out how the juridical review of the judicial review of the Regulation of the Minister of Law and Human Rights number 1 of 2018 concerning paralegals and how to consider the Supreme Court's decision on paralegals based on the decision Number 22 P / HUM / 2018. To find out the considerations in the decision of the Supreme Court Number 22 P/HUM/2018, this study aims to find out the regulation of the Minister of Law and Human Rights number 1 of 2018 concerning paralegals against law number 18 of 2003 regarding advocates. The method used in this research is the study research method, which is a study or study of a problem that has a specific nature, which can be carried out with quantitative or qualitative approaches based on individual goals. This research uses data tools in the form of document studies or library materials that are closely related to research. While the method used is a qualitative approach where this approach produces normative juridical legal writing research. The results of this study indicate that there are similarities in reasons as the basis for the cancellation of the Permenkumham. The Supreme Court has the authority to cancel the Regulation of the Minister of Law and Human Rights. However, the practice of canceling the Regulation of the Minister of Law and Human Rights is contrary to the Decree of the Minister of Home Affairs with the Act and the presidential government system